Bilateral MR-Guided Focused Ultrasound Pallidothalamic Tractotomy for Parkinson's Disease With 1-Year Follow-Up - Gallay, Marc N.; Moser, David; Magara, Anouk E.; Haufler, Fabio; Jeanmonod, Daniel (Frontiers in Neurology, 2021)
Objective: Bilateral stereotactic neurosurgery for advanced Parkinson’s disease (PD) has a long history beginning in the late 1940s. In view of improved lesioning accuracy and reduced bleeding risk and in spite of longstanding caveats about bilateral approaches, there is a need to investigate bilateral MR-guided focused ultrasound (MRgFUS) interventions. We hereby present the clinical results of bilateral pallidothalamic tractotomy (PTT), i.e. targeting of pallidal efferent fibers below the thalamus at the level of Forel’s ﬁeld H1, followed 1 year after operation of the second side. Methods: Ten patients suffering from chronic and therapy-resistant PD having received bilateral PTT were followed one year after operation of their second side. The primary endpoints included the Unified Parkinson’s Disease Rating Scale (UPDRS) scores in on- and off-medication state, dyskinesias, dystonia, sleep disturbances, pain, reduction in drug intake and assessment by the patient of her/his global symptom relief (GSR) as well as tremor control. Results: Time frame between baseline UPDRS score and 1 year after the second side was 36 ± 15 months. Total UPDRS score off-medication 1 year after second PTT was reduced by 52% compared to baseline on-medication (p<0.002). Percentage reductions of the mean scores comparing 1 year off- with baseline on-medication examinations were 91 % for tremor (p=0.0003), 67% for distal rigidity (p=0.007) and 54 % for distal hypobradykinesia (p=0.02). Gait and postural instability were globally unchanged to baseline (13% improvement of the mean, p=0.76 and 5.3 % mean reduction, p=0.90). Speech difficulties, namely hypophonia, tachyphemia and initiation of speech, were increased by 58% (p=0.11 with ANOVA, p=0.06 with Wilcoxon). Dyskinesias were suppressed in 4 over 4, dystonia in 4 over 5 and sleep disorders in 3 over 4 patients. There was an 89% pain reduction. Mean L-Dopa intake was reduced from 690±250 to 110±190. Conclusions: Our results suggest an efficiency of bilateral PTT in controlling tremor, distal rigidity, distal hypobradykinesia, dyskinesias, dystonia and pain when compared to best medical treatment at baseline. There were no statistically significant postoperative changes of axial functions. Larger series are of course needed.